Comparison of compliance with care procedures performed by orthokeratology wearers and their parents and factors affecting compliance. (3rd June 2022) - Yang, Bi; Liu, Longqian; Cho, Pauline
Abstract: Purpose: To compare the levels of compliance with care routines of orthokeratology (ortho‐k) wearers and their parents and to identify factors affecting compliance in a hospital setting in Chengdu, China. Methods: Patients who had worn ortho‐k lenses for at least one month were invited to participate in a survey on compliance. Wearers or their parents were required to complete a questionnaire to determine their compliance with hand hygiene, ortho‐k lenses and accessory care procedures. Results: A total of 200 wearers, 78 male wearers and 122 female wearers, median age 12 (range 8–18) years were enrolled. Except for use of lens solution, the percentage of participants reporting total compliance with all procedures did not differ significantly between lens wearers and their parents. However, compliance for some items was significantly higher when performed by parents p  < 0.001–0.01). 'Eye care practitioner provided instructions' was a significant protective factor for most procedures ( p  < 0.001–0.04). Age and sex were significant risk factors for some items ( p  < 0.001–0.04; p =  0.03–0.04, respectively), with girls having higher compliance than boys. 'Parental supervision' was a significant protective factor for some items ( p =  0.02–0.04) when wearers performed the procedures themselves. When parents performed lens care procedures, only 'eye care practitioner provided instructions' was a significant variable ( p =  0.001–0.04). Conclusion: Some degree of non‐compliance was noted in the majority of ortho‐k wearers, particularly for the care of the lens case and suction holder. Compliance with care of some items was higher when performed by parents. Regular reinforcement of care procedures by practitioners is important, especially for older and male lens wearers. Parental supervision is necessary when children perform lens care procedures themselves, even for older wearers.